Diversified Farming through livestock and agriculture - Boora, A; Singh, Bharat; Yadav, S; Kumar, Anil; Nain, M S; Yadav, Sunita (Indian Farming, 2022)
The farmers sold their quality honey up to ` 220/kg during mela and direct linkage with the consumer. Participating farmers with Farmer FIRST buffalo herd are not only making buffalo farming sustainable and resilient but also getting recognition and growth.